Validation of the Erlangen Test of Activities of Daily Living in Persons with Mild Dementia or Mild Cognitive Impairment (ETAM). Issue 1 (December 2016) - Luttenberger, Katharina; Reppermund, Simone; Schmiedeberg-Sohn, Anke; Book, Stephanie; Graessel, Elmar
Abstract Background There are currently no valid, fast, and easy-to-administer performance tests that are designed to assess the capacities to perform activities of daily living in persons with mild dementia and mild cognitive impairment (MCI). However, such measures are urgently needed for determining individual support needs as well as the efficacy of interventions. The aim of the present study was therefore to validate the Erlangen Test of Activities of Daily Living in Persons with Mild Dementia and Mild Cognitive Impairment (ETAM), a performance test that is based on the International Classification of Functioning and Health (ICF), which assesses the relevant domains of living in older adults with MCI and mild dementia who live independently. Methods The 10 ICF-based items on the research version of the ETAM were tested in a final sample of 81 persons with MCI or mild dementia. The items were selected for the final version in accordance with 6 criteria: 1) all domains must be represented and have equal weight, 2) all items must load on the same factor, 3) item difficulties and item discriminatory powers, 4) convergent validity (Bayer Activities of Daily Living Scale [B-ADL]) and discriminant validity (Mini Mental State Examination [MMSE], Geriatric Depression Scale 15 [GDS-15]), 5) inter-rater reliabilities of the individual items, 6) as little material as possible. Retest reliability was also examined. Cohen's ds were calculated to determine the magnitudes of the differences in ETAM scores between participants diagnosed with different grades of severity of cognitive impairment. Results The final version of the ETAM consists of 6 items that cover the five ICF domains communication, mobility, self-care, domestic life (assessed by two 3-point items), and major life areas (specifically, the economic life sub-category) and load on a single factor. The maximum achievable score is 30 points (6 points per domain). The average administration time was 35 min, 19 of which were needed for pure item performance. The internal consistency was α = .71. The three-week test-retest reliability wasr = .78, and the inter-rater reliability wasr = .97. The ETAM also provided satisfactory discrimination between healthy individuals and persons with MCI or mild dementia as well as between persons with mild and moderate dementia. Conclusions The 6-item final version of the ETAM shows satisfactory psychometric characteristics and can be administered quickly. It is therefore suitable for use in both clinical practice and research.